Monitoring of Insects with Public Participation. Layman's Report - Paolo A. Audisio (Pensoft Publishers, 2017)
The main objective of the LIFE project Monitoring of Insect with Public Participation (MIPP) is to develop and test methods for the monitoring of five species of beetles listed in Annexes II and IV of the Habitats Directive (Osmoderma eremita, Lucanus cervus, Cerambyx cerdo, Rosalia alpina and Morimus funereus). A second objective of the project is the collection of faunistic data, gathered by citizens, via the web and with an app for smartphones. The third aim is to inform and educate the general public on issues such as Natura 2000, Habitats Directive, monitoring and saproxylic insects.